Nonlinear Analysis: Optimization Methods, Convergence Theory, and Applications - Yuan, Gonglin; Yu, Gaohang; Andrei, Neculai; Xiao, Yunhai; Zhang, Li (Abstract and Applied Analysis, 2015)
Table 1 Table 2 We hope that readers of this special issue will find not only convergence results and updated reviews on the common nonlinear analysis, but also important open problems to be resolved such as new formulas in optimization methods, new algorithms for variation analysis and new models for economic problems. [...]large-scale problems in nonlinear equations, semidefinite programming, and image processing are tested to turn out the performance of the new methods.